Assessing the level of awareness and behaviour among a group of Libyans in Benghazi city during the coronavirus (COVID-19) pandemic - M. Ali, Fowziya; F.A. benali, Alla; K Ashour, Juhaynah; Hammad, Fatimah; N. Saleh, Amadalla; Huew, Rasmia; Jebril, Aisha (Libyan Journal of Dentistry, 2022)
Objectives: The study aimed to assess Benghazi Libyan patients' awareness level and behaviour towards the COVID-19 pandemic at the time of the breakthrough of the disease. Methods: A survey using a questionnaire was conducted on 101 adult patients who visited dental clinic services and diabetic centres in Benghazi at the time of breakthrough of the COVID-19 pandemic. Results: The participants were from different age groups (20 to 79) and comprised of males (72.3%) and females (27.7%)who had different education levels. The majority of participants 90 (89.1%) had enough idea about the symptoms of COVID-19 and (84.2%), were aware enough of the direction of COVID-19. Approximately half (49.5%) of respondents affirmed that they didn't have any of the symptoms of COVID-19. Whereas 3% had muscle pain, 5% had a dry cough, and 4% had strong headaches, 6% of participants complained of multiple symptoms of severe headache, dry cough, muscle pain, and loss of sense of taste and smell, 7% complained of fever for two weeks with muscle pain. 7% of participants did not quarantine themselves when they met patients infected with coronavirus symptoms and 8% never quarantined themselves. (89.1%) wear masks outside of their houses, while 48 (47.5%) removed their masks from time to time outside their houses, and 21% reused their masks. (89.1%) did not see a patient with coronavirus while they were aware of the disease. Conclusion: Most of study individuals had adequate knowledge about COVID-19 and were aware of its symptoms. Their behaviour during the pandemic breakthrough was adequate to protect themselves from cross-contamination.